The Influence of Motivation and Organizational Culture on the Performance of the House of Representatives (DPR) With Work Stress as an Intervening Variable in Aceh Province - Muslim syamsuddin; Syaifuddin Syaifuddin; Nagian Toni (Jurnal of Management and Social Sciences, 2023)
The performance of members of the People's Representative Council (DPR) in carrying out their duties is often criticized. Either because of his policies or because of his personality which is considered less effective. Therefore it is necessary to test whether there is an influence of motivation and organizational culture on the performance of the people's representative council (DPR) with work stress as an intervening variable in Aceh Province. This study uses economics, this research is verification. This research refers to the first rule, so the researcher determines the number of samples using the maximum likelihood estimation method of 81 respondents. The results of the study show that motivation has a very large influence on the performance of the Aceh Province DPR. Because with the motivation of the DPR, they will have enthusiasm in working and carrying out the assigned tasks. In addition, organizational culture also has a very large influence on the performance of the Aceh Provincial Parliament. Because with relevant habits in carrying out their duties. Then the work that has been set will be easier to do. So it can be concluded that motivation and organizational culture have a very large influence on the performance of the Aceh DPR.